What is the significance of importance performance in the context of a hospital? - Qurratul Aini; Elsye Maria Rosa (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Importance-performance analysis (IPA) is a method that can be used for management to help prioritize developing and improving service quality based on customer ratings. This study aims to determine the performance and patient satisfaction level in one of public hospital in Indonesia using IPA method by using data patient satisfaction survey with total 572 patients as respondents. The service unit becoming the object of research which is measured the patient’s performance and level of satisfaction. The results show that aspects of administrative services in the emergency room, maternity, radiology, and rehabilitation units need to improve service satisfaction with treatment requirements and procedures. The results also indicate that level of performance of the health service unit in the hospital as a whole is good.